Konsep Hukum Islam dalam Penanggulangan Konflik dan Bentrok Fisik di Indonesia - Nurhasmi N; Abd. Qadir Gassing; Abd. Rahman R. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the concept of Islamic law in addressing conflict and physical violence in Indonesia. Conflict and physical clashes are unavoidable social phenomena, occurring in both private and public spheres, arising from political, economic, religious, and cultural factors. This research employs a descriptive qualitative approach using library research methods, analyzing classical and contemporary literature related to conflict theory and Islamic legal perspectives. The findings indicate that Islamic law offers a comprehensive framework for conflict resolution, encompassing preventive approaches through da'wah, curative measures through tabayyun, musyawarah and sulh, as well as principles of tasamuh and al-afwu, and tahkim and islah. These concepts emphasize not only conflict resolution but also the development of social awareness, tolerance, and peace, which are highly relevant in the context of modern Indonesian society. The study concludes that Islamic law provides an effective normative and practical framework for mitigating conflict and physical violence, while fostering moral and social awareness to prevent destruction and violence.